Severe Uncompensated Metabolic Alkalosis due to Plasma Exchange in a Patient with Pulmonary-Renal Syndrome: A Clinician’s Challenge - Mohsin Ijaz; Naeem Abbas; Dmitry Lvovsky (Case Reports in Critical Care)
Metabolic alkalosis secondary to citrate toxicity from plasma exchange is very uncommon in patients with normal renal function. In patients with advanced renal disease this can be a fatal event. We describe a case of middle-aged woman with Goodpasture’s syndrome treated with plasma exchange who developed severe metabolic alkalosis. High citrate load in plasma exchange fluid is the underlying etiology. Citrate metabolism generates bicarbonate and once its level exceeds the excretory capacity of kidneys, the severe metabolic alkalosis ensues. Our patient presented with generalized weakness, fever, and oliguria and developed rapidly progressive renal failure. Patient had positive serology for antineutrophilic cytoplasmic antibodies myeloperoxidase (ANCA-MPO) and anti-glomerular basement membrane antibodies (anti-GBM). Renal biopsy showed diffuse necrotizing and crescentic glomerulonephritis with linear glomerular basement membrane staining. Patient did not respond to intravenous steroids. Plasma exchange was started with fresh frozen plasma but patient developed severe metabolic alkalosis. This metabolic alkalosis normalized with cessation of plasma exchange and initiation of low bicarbonate hemodialysis. ANCA-MPO and anti-GBM antibodies levels normalized within 2 weeks and remained undetectable at 3 months. Patient still required maintenance hemodialysis.